Retrieval of electrical and physical properties of dielectric samples using time-domain multiple reflection method - Aman; Singh V.; Bhattacharyya S. (My University, 2025)
In this study, a novel time-domain multiple reflection method for determining the electrical properties and thickness of the sample has been proposed. The unique advantage of this method is that it employs only reflection coefficient data for the reconstruction of the properties. The proposed scheme is validated by determining the permittivity, thickness, and loss tangent values of different samples of different thicknesses with high accuracy. The experimental characterisation has been carried out, incorporating the proposed scheme for its verification and thereby the electrical and physical properties of an unknown sample have been retrieved. The proposed method is simple, cost-effective and non-iterative in nature. The proposed technique is quite useful in applications like through-wall imaging, where the wall can be accessed from a single side only, monitoring the health of the building and ground-penetrating radar. © The Institution of Engineering and Technology 2020